THE USE OF CITRIC ACID MODIFIED BACTERIAL CELULLOSE AS AN ENVIROMENTALLY FRIENDLY ADSORBENT - Diah Mardiana; Ani Mulya Suryani; Budi Kamulyan; Nur Lailatul Rahma (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
AbstractThe use of nata de coco as an ester cellulose raw material through esterification using various of carboxylic acids has been widely conducted. In this study, it was used citric acid with three carboxyl groups. This aim research were to determine the optimum reactant composition and to compare the cellulose citrate properties toward bacterial cellulose and commercial ester cellulose. Esterification at mass ratio of nata : citric acid were 1 : 1 up to 1 : 9 were conducting at temperature of 150oC. The optimum ester cellulose produced, were then characterized based on the FTIR spectrophotometry, hydrophobicity and degree of crystallinity. Furthermore, the surface area has been determined in order to find out its potency as an adsorbent .The result revealed that reaction using citric acid has affect on chemical structure and hydrophobicity. The increase of hydrophobicity and degree of crystallinity was influenced by citric acid added. On the other hand, it was obtained that cellulose citrate could be develop as an adsorbent.Keyword: cellulose, esterification, citric acid, adsorbent